Description and disposition of home patients with colorectal cancer accessing a practical, complications related medication therapy management service - Wang, Qinbo; Zhou, Yuan; Li, Hua; Ou, Yingjuan; Fei, Jiaxi; Wu, Xia; Chen, Junrong; Li, Xiaoyan (Frontiers in Oncology, 2025)
ObjectiveTo explore a practical complications related Medication Therapy Management (MTM) service for colorectal cancer patient which based on take home cancer drugs (THCDs), and minimize the occurrence of unexpected events by reducing complications and adverse reactions in home therapy.MethodA total of 144 patients with colorectal cancer (CRC) who underwent home cancer drugs treatment for the first time met the include criteria from July 1, 2023 to July 31, 2024. They were divided into control group and MTM intervention group randomly, MTM intervention group conducted with three courses of MTM intervention, and control group adapt with three times of conventional follow up. We compared patient characteristics, complications, adverse effects, and knowledge-practice-attitude (KPA) results.ResultsAmong them, 119 patients were enrolled. There were significant differences regard of cancer pain, insomnia, anxiety, and defecation disorder (p<0.05); Multivariate analysis results showed that pain, chemotherapy-induced nausea or vomiting (CINV), and defecation disorder were independent factors for unscheduled hospital admission (p<0.05); There were significant differences regard of adverse effects for home medication patient which include jaundice, hypo leukocytosis, limb edema, and fatigue (p<0.05); MTM intervention group showed better feedback than control group in Attitudes and practice Toward screening (p<0.05).ConclusionMTM demonstrates significant clinical benefits in colorectal cancer (CRC) patients by effectively reducing the incidence of treatment-related complications, including nausea and vomiting (CINV), abdominal pain, and insomnia. Furthermore, it contributes to decreased rates of unplanned hospitalization and enhances key patient outcomes (KPA), warranting further investigation and clinical application in CRC management.